Art in and out of context (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
This article discusses the role of context in arts and aesthetic theory and demonstrates that contextual analysis broadens our understanding of these two realms. It demonstrates a codification of an important controversy in aesthetic theory and arts between formalist and contextualist theories. It serves as a means to highlighting some moments in the development of aesthetics and arts that contributed to the rejection of old paradigms (disinterest theory, formalism) and instigated a move towards a more context-focused analyses of art and aesthetics.